DAMPAK KEBERADAAN TEMPAT PEMBUANGAN AKHIR (TPA)TERHADAP KONDISI SOSIAL MASYARAKAT DUSUN NGABLAK,DESA SITIMULYO, KECAMATAN PIYUNGAN, KABUPATEN BANTUL - Novia Harum Solikhah, Ahmad Syaiful Hidayat, dan Alvian Angga Nur Ardian (Pelita - Jurnal Penelitian Mahasiswa UNY, 2011)
The aims of the research were to reveal the daily social activities of the people living around alandfill and to find out the impact of the existence of a landfill of Piyungan Bantul on the condition of thesurrounding society.The reserach method used was descriptive qualitative. The data were collected throughinterviews and observations. The respondents of the interviews were the manager of the landfill ofPiyungn, the head of the dusun, the head of the neighbourhood organization, the chief of the mosquecaretakers, the chief of the scavenger organization, the people of Dusun Ngablak and some scavengers.In conducting the observation, the reserachers used an observation guide, namely the observation on theinteraction of the people in the society, how the members of the society invilve themselves in the sociallife, and how the scavengers work in the landfill. The type of observation was partial participativeobservation.The result of the research showed that the impact of the landfill on the social activities was thatit brought extra activities for the people such as working as scavengers, running small shops, and raisingcattle. The impacts on the social condition of the society were that the people’s economy was gettingbetter, the unemployment rate decreased, the people’s quality of life improved. Environmentally, thelanfill caused pollution to the environment and air pollution. In terms of health, people did not careabout the landfill as they considered it as somthing common. In the aspect of social life, the people livingaround the landfill did not have good communication and interaction with their neighbours as they werebusy with their own jobs. In relation to education, parents did not give enough attention to theirchildren’s education because they spent more time in the landfill to get rupiahs. They believed that thelandfill is a field of gold.Key words: landfill, social condition, society